If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12d + 11 = 27 Reorder the terms: 11 + 12d = 27 Solving 11 + 12d = 27 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 12d = 27 + -11 Combine like terms: 11 + -11 = 0 0 + 12d = 27 + -11 12d = 27 + -11 Combine like terms: 27 + -11 = 16 12d = 16 Divide each side by '12'. d = 1.333333333 Simplifying d = 1.333333333
| 2x^2-1=8x | | 9(x-2)=-36 | | 0.5x-0.3(2-x)=4.2 | | 6.5/3x+5=11 | | -d+43-2d=9 | | 10x-46=8x-30 | | 49x^2+14x+1=3 | | -7/10+(-3/5) | | 8-3x+1=4x+2 | | 4x^2-10=9x | | i^42=0 | | 0.5-0.3(2-x)=4.2 | | 2(-1)+y=2 | | 4x^2+20x+25=81 | | x^2+21x-1024=0 | | 80-9/2x=0 | | 3(-1)-y=-7 | | 80-9/2x=0 | | x-8.6=-6.7 | | 2x^2-56=0 | | 10/25 | | t+28=21 | | 2h+3s=145 | | (-y^2-3y-5)-(-3y-7y+4)= | | -5(9)-5y=-50 | | c+9=3 | | 3/7+2/5 | | x^2-18x=7 | | 4x+15=5x+12 | | 27-5x=x+13 | | (7x-6y)+(3x+3y-3)= | | -9-5y=-50 |